The complete mitochondrial genome of Sparus aurata (Perciformes: Sparidae) with phylogenetic consideration. Issue 1 (2nd January 2019) - Ma, Xilan; Xie, Zhenzhen; Zhou, Libin; Zhang, Xiaogu
Abstract: The complete mitochondrial genome of the Sparus aurata was presented in this study. The mitochondrial genome is 16, 652 bp long and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. The gene order and composition of S. aurata mitochondrial genome were similar to that of most other vertebrates. The nucleotide compositions of the light strand in descending order is 28.84% of G, 27.26% of A, 26.77% of T and 17.13% of C. With the exception of the NADH dehydrogenase subunit 6 (ND6) and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. The phylogenetic analysis by maximum-likelihood (ML) method showed that the Sparus aurata has the closer relationship to the Rhabdosargus sarba in the phylogenetic relationship.